Proton exchange membrane water electrolysis system-membrane electrode assembly with additive. (14th June 2019) - Yu, Jyun-Wei; Jung, Guo-bin; Su, Yi-Ju; Yeh, Chia-Chen; Kan, Min-Yu; Lee, Che-Yu; Lai, Chun-Ju
Abstract: In proton exchange membrane water electrolysis system, the performance is highly affected by the anode materials and the operation modes. In addition, high voltages are for higher hydrogen production and also ozone for disinfection. After switching off of the power and restarted, a decrease in electric conductivity may lead to a performance drop in further hydrogen/ozone/generation. In this study, three different additives, A, Z and V are adopted which respectively mixed with the PbO2 and to become anode catalyst ink. The characteristics of the anode catalysts are determined by interruptive power supply, electrochemical impedance spectroscopy, and cyclic voltammetry tests. The results show that additives A and Z have batter current efficiency than the other groups. Additionally, anode catalyst withadditive V possess the most outstanding durability among all groups. Highlights: Performance declined after power interrupted and restored has been solved. Additives A and Z have better current/performance. Additives V reduces the damage on power interruption and restores operation. Additives catalyst inks are better than commercial one.